The Role of Sheikh Dr. H. Abdul Karim Amrullah in Developing Muhammadiyah in Maninjau West Sumatera - Muslim Muslim; Ihsan Ihsan (Universitas Muhammadiyah Mataram, 2018)
This study aims to describe the role of Sheikh Dr. Abdul Karim Amrullah in developing Muhammadiyah in Maninjau. This type of research is qualitative research with historical methods, and heuristic measures, source criticism, interpretation, and historiography. The theory and approach in this research is the phenomenological approach and the theory of study figures. The results obtained from this study first, Sheikh Dr. H. Abdul Karim was a scholar who was born in 1879 Ad and died in 1945 A.D. He was born to a religious family, since childhood he has received a religious education from both parents and then continued his education through non-formal course. Secondly, the role of Sheikh Dr. H. Abdul Karim Amrullah in developing Muhammadiyah in Maninjau, backed by the religious condition of Maninjau that time has been mixed only, is no longer distinguished where the teachings of pure Islam and which are mixed with bid'ah, and Khurafat. This is what prompted Sheikh Dr. H. Abdul Karim Amrullah to make updates to Islam that has been corrupted in Maninjau. Therefore, to accelerate this renewal. He was the pioneering establishment of Muhammadiyah in Maninjau, after his return from Java in 1925 A.D.